Airborne Temperature Survey of Harrison Bay - Hufford, Gary L.; Bowman, Richard D. (ARCTIC, 1974)
During 10 August 1973 while conducting an oceanographic program in deep waters off the North Slope of Alaska, an opportunity arose to make an airborne radiation thermometer (ART) flight to map the surface water temperature of Harrison Bay . Little is known about the oceanography of the Bay. Yet this zone may well come under considerable, if not great, environmental stresses stemming from present localization of resource development and exploitation. This paper presents a summary of the results of the low-altitude ART flight. . A Barnes Engineering Company PRT-5, 9.5-11.5 µ Infrared Radiometer with a field of view of 2 degrees was used . The temperature survey was carried out using 2 helicopters . flying a grid pattern and measuring the surface temperature along the flight track. The flight was conducted at a nominal altitude of 46 metres, with a flight speed of 150 km/hr. Navigation was done by visual contact with the coast and by radar tracking from the Glacier. Clear, cloud-free conditions existed in the entire study area during the survey. Continuous winds (>3.0 m/sec) mixed the surface waters so that the radiometer measurements are representative of bulk temperature rather than the skin temperature of the water. The ART equipment was calibrated before, during, and after the flight. . Contours of the surface-water temperature distribution of Harrison Bay are presented . Two major features are exhibited: the lack of large river effluent plumes; and the penetration of relatively cold water from the west into Harrison Bay. The weak packing of isotherms (4° to 8°C) near the Colville River delta indicates that river runoff was very low in early August and freshwater influence was restricted to near the shore. This was expected. . the Colville River has a total annual discharge of 16 × 10**9 m³ of which 80 per cent occurs the first twenty days of June. During the rest of the summer, river flow is very low. In the second feature . the 3°C isotherm represented the boundary of the cold water and was ...